Influence Diameter Variation of Lime Column Above Sand Column In Soft Clay Soil Stabilization - Ermawan, Dadis (2016)
There are various types of soil one of them is soft clay soil. This soil type has poor characteristics, usually characterized by extreme water content, large compressibility, and small permeability coefficient. If we are going to construct a building in areas that have poor soil characteristics, so we must improve the characteristics of soil first because if directly used to construct the building will be in danger. At this research, soil stabilization from Troketon village, Pedan districts, Klaten regency of Central Java Indonesia using vertical drain lime column above sand column with diameter variation 10 cm and 20 cm. From each diameter taken 6 samples. From distance 16.67 cm of column, take 1 sample from lime zone, 1 sample from zone between lime-sand, and 1 sample from sand zone. From distance 50 cm of column also take same sample like from distance of column 16.67 cm. This research aims to determine the effect of lime column above sand column on soft clay soil in terms of mechanical and physical properties. From the research, soil stabilization using lime column above sand column have improved the soil properties. For mechanical properties, it's can increase the Cv value and decrease the Cc and Sc value. And for physical properties it's can decrease the specific gravity (Gs) value, LL value, and PI value. Also Increase the PL value and SL value. Getting close to the column, is the better effect on the characteristics of soil. As well as bigger diameter of column which is used to stabilized the soil is more effective to improve the soil characteristic.